2012
DOI: 10.1186/1475-2859-11-115
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive and quantitative review of dark fermentative biohydrogen production

Abstract: Biohydrogen production (BHP) can be achieved by direct or indirect biophotolysis, photo-fermentation and dark fermentation, whereof only the latter does not require the input of light energy. Our motivation to compile this review was to quantify and comprehensively report strains and process performance of dark fermentative BHP. This review summarizes the work done on pure and defined co-culture dark fermentative BHP since the year 1901. Qualitative growth characteristics and quantitative normalized results of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
98
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(99 citation statements)
references
References 327 publications
(172 reference statements)
1
98
0
Order By: Relevance
“…The hydrogen yields (Y H2/S ) obtained in the present study lie within the range of data reported in a review of dark fermentation published by Rittmann and Herwig (2012). However, the hydrogen productivity obtained for all three reactor sizes were relatively low (0.6 to 3.2 mmol/L/h) when compared to the range reported in the same review (2.09 to 27.1 mmol/L/h).…”
Section: Hydrogen Yield Obtainedsupporting
confidence: 86%
“…The hydrogen yields (Y H2/S ) obtained in the present study lie within the range of data reported in a review of dark fermentation published by Rittmann and Herwig (2012). However, the hydrogen productivity obtained for all three reactor sizes were relatively low (0.6 to 3.2 mmol/L/h) when compared to the range reported in the same review (2.09 to 27.1 mmol/L/h).…”
Section: Hydrogen Yield Obtainedsupporting
confidence: 86%
“…The involvement of Clostridium species in H2 production is well known and they are reported to be able to use several waste matrices [1,53]. Various strains of C. beijerinckii were isolated from several sources but, interestingly, the hydrogen production yield of the strain isolated here is higher than those previously reported [54][55][56].…”
Section: Staphylococcusmentioning
confidence: 63%
“…There are numerous review articles describing the impact of genomics and metagenomics methods on microbial ecology (Xu 2006, Binga, Lasken et al 2008, Aziz, Breitbart et al 2010, Gilbert and Dupont 2011, Rittmann and Herwig 2012, Su, Lei et al 2012, Thompson, Field et al 2013, Reid 2014, Tseng and Tang 2014. There is also a plethora of papers that discuss the application of metagenomics in the field of biotechnology to discover novel enzymes, drug molecules, processes and applications (Lorenz, Liebeton et al 2002, Schloss and Handelsman 2003, Cowan, Meyer et al 2005 Eck Kennedy, Marchesi et al 2007, Brady, Simmons et al 2009, Steele, Jaeger et al 2009, Piel 2011, Iqbal, Feng et al 2012, de Castro, Sartori da Silva et al 2013, Hicks and Prather 2014.…”
Section: Why Is This Review Timely?mentioning
confidence: 99%